ANALISIS KONTRASTIF KATA GANTI ORANG BAHASA INGGRIS DAN BAHASA YALI - KOBAK, KOPMAHUN KONNI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT English and Yalilanguage are two languages of different language families. English belongs to Indo- European group, whereas  Yali language belongs to the lingua Malanesian Austronesian one. Each of them has its own characteristics. This study is an attempt to describe and contrastthe  aspectand the using of language, that is, the pronouns. The method applied by the writer in this study is the theory of  Bloomfield and Aarts and Aarts theory to describe the two languages and Lado’  concepts to contrast them. This result shows that English has eight kinds of pronouns namely: personal pronouns, demonstratives pronouns,  self relative pronouns, possesive pronouns, interrogative pronouns, masculine and feminine pronouns. The Yali Language  comprises eight kinds of pronouns namely:personal pronouns, demonstrative pronouns, self pronouns, relative pronouns, interrogative pronouns. Both English and Yali language have first, second, and third person singular and plural.  In the noun phrase these pronouns function as head and determinerand than as post modifier in the structure of noun phrase whereas inthe sentence they function as subject and object Key words A  Contrastive Analysis, English and Yali  language.